The effect of teaching text organisation on reading in English as a second language - Silburn, Gail Deirdre (Rhodes University, Faculty of Education, Department of Education, 1991)
This research investigated the effect of teaching text organisation on reading in English second language to schoolgirls. All subjects underwent a training programme of five one-hour sessions on consecutive school days. The experimental group were trained in the use and recognition of top-level organisation as a reading strategy, based on work done by Bartlett (1978) and Carrell (1985). The control group were trained in unrelated grammar exercises. A pre-test was administered to each group before their programme began. Post-test 1 was administered immediately after the training was completed, and Post-test 2, three weeks later. These tests required a written recall of two passages once they had been read, and an answer to a question on their organisation. The null hypotheses stated that the experimental group's training in the use and recognition of top-level organisation as a reading strategy would make no difference in their ability to read and recall information or to recognise and use top-level organisation in their recalls. For the quantity of information recalled, no differences were found in the Pre-test and Post-test 1; a statistically significant difference was found in Post-test 2 in favour of the experimental group. For the quality of information recalled, the control group remembered more top-level idea units in the Pre-test; there was no difference in Post-test 1; the experimental group did better in three out of five levels in Post-test 2. There was no difference in the Pretest in either group's use of the passage's top-level organisation to structure recalls, but the experimental group did better in both post-tests. The control group did better in the Pre-test in recognising the passage's top-level organisation, but the experimental group did better in both post-tests. The null hypotheses were rejected as the experimental training made a difference, although this difference only became apparent three weeks later, and not immediately after the training. The experimental group's nullifying the control group's Pre-test advantage in Post-test 1 and surpassing it in Post-test 2, powerfully supports Bartlett's and Carrell's findings that teaching the strategy did make a difference and that this effect could be maintained over three weeks
Keywords: English language -- Study and teaching -- Foreign speakers